Vaccinology: Design, Development and Approvals - Aziz-Andersen, Kaiser Jay (Journal of Drug Delivery and Therapeutics, 2022)
The goal of vaccine design and development is to manufacture and consistently produce a vaccine that is safe and effective. The vaccine discovery starts with design input in terms of identification of etiologic agent, immunogenicity, adjuvant, basic scientific concepts, non-clinical and clinical studies, and finally vaccine licensure (FDA approvals). The administering regimens are studied in clinical research laboratory and study materials are tested in suitable bench testing and biological models projecting vaccine candidate’s prophylactic immune response that is safe and effective. The vaccine manufacturing process requires critical quality control points (CQCPs) monitoring in order to maintain the steriochemical and immunological characteristics of the vaccine molecules and enable production of the vaccine in increasingly dosage quantities for ultimate human use. These aspects of vaccine development are well integrated into the total vaccinology life cycle (TVLC) regulatory requirements. The ultimate regulatory safety and efficacy requirements of the vaccine are proven through phases of clinical trials (class I, II, and III studies). The final process for human use to produce safe vaccine is part of pivotal clinical trials and data under the US FDA’s premarket approval process for full-scale production and availability of safe vaccines for clinical use.Keywords: vaccine design and development, etiologic agent, immunogenicity